Study on the Anatomy of Young Coffee Plants from Micro-Cuttings and Induced to Sprout (Plant Tissue Culture and Biotechnology, 2019)
Micro-cuttings coming from Catucaí coffee plants were established in the greenhouse and treated to sprout by decapitation and application of 600 mg/l triiodobenzoic acid. The morphology and the anatomy of treated and control plants were compared. Treated plants produced only orthotropic sprouts, useful for micro-cutting, while control plants produced only plagiotropic sprouts. Direct connections between the orthotropic sprouts and the petiole accessory veins were observed only in treated plants. All together, these results were interpreted as consequences of disturbances in the auxin transport systems, which shape apical dominance and bud dormancy.